The online mastermind game / Cheong Kuen Leion - Cheong, Kuen Leion (2003)
This online Mastermind game project is developed to give the chances to people from all arround the world to play with each other though the are not known each other: Besides that, this project is also to test the effectiveness of the technique, which is called as Genetic Algorithm on solving a problem. In the other words, the aim of this project is to develop an online Mastermind game using genetic algorithm between a computer and a player or (ideally) a group of players over the network. This game will let the player feel more comfortable and they can imagine that they are playing with another virtual player. Besides that, the player can even know and practice how the computer system is going to solve the puzzles by using the genetic algorithm by showing some hint to the player during the game. This game shows the basic concept that is used in solving problems.